Theoretical and experimental investigation of a novel multistage evacuated solar still - Abakrb, Yousif A.; Ismail, Ahmad Faris (Journal of Solar Energy Engineering, Transactions of the ASME, 2005)
Solar desalination is an ideal source of fresh water for both drinking and agriculture. A lot of research was conducted on solar desalination systems, but most of the available systems have low production, are expensive, and are not reliable for long term use. In this work a new multistage evacuated solar desalination system was proposed and designed.The objective of this work is to increase the productivity and improve the low efficiency of the traditional solar desalination systems. The new system works by virtue of the higher evaporation rate under vacuum condition inside the solar still. A model for the system was developed and used to optimize the system design. The new model was subjected to a Finite Element Analysis (FEA) structural analysis using MSC/NASTRAN™ FEA software. A Computational Fluid Dynamics (CFD) simulation of the evaporation and condensation process inside one stage of the new solar still was conducted using FLUENT™ software. The system prototype was fabricated and tested at the actual outdoor ambient conditions for a period of 3 months. The productivity of this new system was found to be 14.2 kg/m2/day, which is about threefold of the maximum productivity of the basin type solar still. The cost of produced still water is estimated as 0.20 US$/gal. The results show that the multi-stage evacuated solar still might be a good option as a solar desalination system.